Low-temperature-resistant waterproof coating for outer wall of house building and preparation process of low-temperature-resistant waterproof coating
By combining modified silicone-acrylic emulsion with polyurethane-acrylate core-shell emulsion and polyether polyol modified nanofillers, a multi-scale stress dissipation network is constructed, which solves the problems of high brittleness and insufficient flexibility of traditional coatings at low temperatures, and achieves high strength and durability improvement of the coating film.
Patent Information
- Application Number
- CN202511676063.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-17
- Publication Date
- 2025-12-12
- Estimated Expiration
- 2045-11-17
AI Technical Summary
Traditional exterior wall waterproof coatings are brittle and lack flexibility in low-temperature environments, making the coating film prone to cracking and unable to effectively resist freeze-thaw cycles and stress changes under extreme northern climate conditions.
A strong and elastic composite matrix is formed by using modified silicone-acrylic emulsion and polyurethane-acrylate core-shell emulsion. Combined with polyether polyol modified nanofiller and rubber nanopowder, a multi-scale stress dissipation network is constructed to enhance the low-temperature toughness and durability of the coating.
It maintains excellent elasticity and durability in low-temperature environments, improves the elongation at break, impact resistance and anti-sagging properties of the coating, and enhances the adhesion and durability of the coating.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the technical field of coatings, and more specifically, it relates to a low-temperature resistant waterproof coating for exterior walls of buildings and its preparation process. Background Technology
[0002] Exterior wall waterproofing is a core component in ensuring the durability and safety of building structures, especially in northern regions where the climate poses extremely severe challenges to waterproofing systems. Long winters are accompanied by persistent low temperatures, frequent freeze-thaw cycles, and extreme weather events such as strong winds and snowfall, requiring waterproofing coatings to possess weather resistance, flexibility, and freeze-thaw stability far exceeding those in southern regions. Traditional exterior wall waterproofing coatings, such as asphalt-based and ordinary acrylic products, typically have a glass transition temperature (Tg) above 0°C. While they are rigid at room temperature, once the ambient temperature drops below their Tg, the molecular chain movement freezes, and the material transitions from a highly elastic state to a glassy state, thus losing its flexibility. This transition manifests directly at low temperatures as a hardening and brittleness of the coating film. When encountering even minor thermal expansion and contraction or frost stress on the substrate, it is highly susceptible to brittle cracking and delamination from the substrate. Once the waterproofing layer fails, moisture will seep into the wall, causing not only dampness and mold growth on the interior walls, but more seriously, when moisture penetrates into the concrete, it can cause corrosion and frost damage to the internal steel bars, endangering the building's safety and lifespan from a structural perspective.
[0003] Patent application CN119570324A discloses a nano-coating that is resistant to high and low temperatures and acids and alkalis, comprising the following raw materials in parts by weight: 30-40 parts of pure acrylic emulsion, 10-20 parts of modified nano-silica, 2-4 parts of nano-titanium dioxide, 3-6 parts of nano-zinc oxide, 2-4.4 parts of additives, and 5-9 parts of water. The modified nano-silica is nano-silica modified with a modifier, which includes diesters and / or diols.
[0004] While this approach modifies nano-silica with diesters and / or diols to some extent, improving material compatibility, the high total amount of inorganic phase in the formulation leads to increased coating brittleness and decreased elongation at break. This embrittlement trend will be further exacerbated, especially in low-temperature environments in northern regions, affecting the mechanical properties and long-term durability of the coating. Furthermore, the system uses only pure acrylic emulsion as the film-forming material, which is insufficient in terms of freeze resistance and flexibility maintenance, making it difficult to fully meet the requirements of use under extreme temperature fluctuations. Summary of the Invention
[0005] In order to overcome the problems of high film brittleness and insufficient low-temperature toughness caused by the high amount of inorganic nanomaterials and the single film-forming substance in the existing technology, and to further improve the mechanical properties and low-temperature resistance of waterproof coatings, this application provides a low-temperature resistant waterproof coating for building exterior walls and its preparation process.
[0006] In the first aspect, this application provides a low-temperature resistant waterproof coating for exterior walls of buildings, employing the following technical solution: A low-temperature resistant waterproof coating for exterior walls of buildings is prepared from the following raw materials in parts by weight: 200-250 parts of modified silicone-acrylic emulsion, 75-125 parts of polyurethane-acrylate core-shell emulsion, 40-60 parts of polyether polyol modified nanofiller, 15-25 parts of rubber nanopowder, 10-20 parts of liquid polyisoprene, 22-34 parts of additives and 60-100 parts of composite solvent. The modified silicone-acrylic emulsion is specifically prepared by prepolymerizing a polyhydroxy compound containing double bonds and a silane coupling agent containing double bonds, and then copolymerizing it with acrylate monomer A and vinyl fluorosilicone oil. The polyurethane-acrylate core-shell emulsion is specifically formulated by prepolymerizing polyether polyol, isocyanate, and carboxyl-containing hydrophilic monomer, followed by copolymerization with acrylate monomer B.
[0007] In this scheme, a strong and elastic composite matrix is first formed by modifying silicone-acrylic emulsion and polyurethane-acrylate core-shell emulsion. Polyether polyol modified nanofiller achieves a combination of rigidity and flexibility through a flexible interface. At the same time, rubber nanopowder and liquid polyisoprene synergistically construct a multi-scale stress dissipation network to ensure that the coating maintains excellent elasticity and durability in low-temperature environments.
[0008] Preferably, the solid content of the modified silicone-acrylic emulsion is 50% to 55%.
[0009] Preferably, the solid content of the polyurethane-acrylate core-shell emulsion is 50% to 55%.
[0010] Preferably, the composite solvent includes water and an organic solvent.
[0011] Preferably, the mass ratio of water to organic solvent is 1:(1~1.5).
[0012] Preferably, the organic solvent includes propylene glycol methyl ether and isopropanol.
[0013] Preferably, the preparation method of the modified silicone-acrylic emulsion includes the following steps: Under an inert atmosphere, the composite solvent and emulsifier are mixed evenly, then a polyhydroxy compound containing double bonds and a silane coupling agent containing double bonds are added and mixed evenly. The mixture is heated to 70-90°C, a portion of the initiator is added, and the reaction is carried out for 60-90 minutes. Then, acrylate monomer A, vinyl fluorosilicone oil and the remaining initiator are added, and the mixture is kept at this temperature for 4-5 hours. After vacuum distillation and cooling, the solid content is adjusted to obtain the modified silicone-acrylic emulsion.
[0014] In this scheme, during the prepolymerization stage, a polyhydroxy compound containing double bonds and a silane coupling agent containing double bonds undergo free radical copolymerization to form a prepolymer with polymerizable double bonds, hydroxyl groups, and hydrolyzable alkoxy groups, laying the foundation for subsequent copolymerization and interfacial bonding. During the copolymerization stage, this prepolymer is further copolymerized with acrylate monomers and vinyl fluorosilicone oil to ultimately obtain a composite emulsion with a unique microstructure. In this emulsion, organosiloxane segments enhance molecular chain flexibility, the groups in the vinyl fluorosilicone oil impart durable hydrophobicity to the coating film through surface migration effects, and the abundant hydroxyl groups provide numerous hydrogen bonding sites. This allows the emulsion to form strong interactions with the active groups in the core-shell emulsion during subsequent coating film formation, and also to form interfacial bonds with modified nanofillers and other components through hydroxyl groups, jointly constructing a stable three-dimensional network structure, thereby significantly improving the low-temperature toughness, adhesion, and durability of the coating film.
[0015] Preferably, the mass ratio of the double-bonded polyhydroxy compound, the double-bonded silane coupling agent, the acrylate monomer A, and the vinyl fluorosilicone oil is (32~48):(12~40):(300~340):(20~32).
[0016] Preferably, the polyhydroxy compound containing a double bond is either trimethylolpropane diallyl ether or pentaerythritol triallyl ether.
[0017] Preferably, the double-bonded silane coupling agent is either vinyltrimethoxysilane or vinyltriethoxysilane.
[0018] Preferably, the acrylate monomer A includes butyl acrylate, monobutyl maleate, and dodecafluoroheptyl methacrylate.
[0019] Preferably, the mass ratio of butyl acrylate, monobutyl maleate, and dodecafluoroheptyl methacrylate is (240~260):(20~30):(40~50).
[0020] Preferably, the initiator is ammonium persulfate or potassium persulfate.
[0021] Preferably, the amount of the initiator is 0.8% to 1.2% of the total mass of the polyhydroxy compound containing double bonds, the silane coupling agent containing double bonds, the acrylate monomer A, and the vinyl fluorosilicone oil.
[0022] Preferably, the method for preparing the polyurethane-acrylate core-shell emulsion includes the following steps: Under an inert atmosphere, polyether polyol, isocyanate, carboxyl-containing hydrophilic monomer, catalyst, and acetone are added to a reactor, heated to 60-80°C, reacted for 2-4 hours, cooled, and the pH is adjusted to 7.5-8.0. The mixture is then added to water containing emulsifier, mixed thoroughly, heated to 70-90°C, acrylate monomer B and initiator are added, and the mixture is kept at this temperature for 2.5-3.5 hours. The mixture is then distilled under reduced pressure, cooled, and the solid content is adjusted to obtain a polyurethane-acrylate core-shell emulsion.
[0023] Preferably, the mass ratio of the polyether polyol, isocyanate, carboxyl-containing hydrophilic monomer and acrylate monomer B is (50~60):(25~35):(3~4):(40~60).
[0024] Preferably, the carboxyl-containing hydrophilic monomer is dimethylolpropionic acid.
[0025] Preferably, the acrylate monomer B includes butyl acrylate, methyl methacrylate, and monobutyl maleate.
[0026] Preferably, the mass ratio of butyl acrylate, methyl methacrylate and monobutyl maleate is (25~30):(10~20):(5~10).
[0027] Preferably, the initiator is ammonium persulfate or potassium persulfate.
[0028] Preferably, the amount of the initiator is 0.8% to 1.2% of the mass of acrylate monomer B.
[0029] In this scheme, under an inert atmosphere, a polyurethane prepolymer is first formed using polyether polyol and isocyanate as core raw materials to construct a highly elastic core layer, laying the foundation for low-temperature crack resistance. Then, acrylate monomer B and an initiator are added at elevated temperatures for copolymerization, forming an acrylate shell layer on the surface of the polyurethane prepolymer particles. Methyl methacrylate, as a rigid monomer, imparts hardness and strength to the shell layer, while butyl acrylate, as a flexible monomer, ensures the shell layer's toughness. The carboxyl groups provided by monobutyl maleate not only stabilize the latex particles but also serve as reaction sites for subsequent bonding with carbodiimide, thereby strengthening the core-shell interface and participating in the construction of the overall cross-linked network of the coating film, synergistically achieving both low-temperature resistance and high strength.
[0030] Preferably, the preparation method of the polyether polyol modified nanofiller includes the following steps: Under an inert atmosphere, the acidified nanofiller is uniformly dispersed in an organic solvent, a catalyst is added and mixed evenly, then polyether polyol is added and mixed evenly. The mixture is heated to 80~100℃ and reacted for 4~6 hours. After cooling, solid-liquid separation is performed, followed by washing and drying to obtain polyether polyol modified nanofiller.
[0031] Preferably, the acidified nanofiller is specifically treated with dilute nitric acid.
[0032] A further preferred embodiment of the method for preparing the acidified nanofiller includes the following steps: The nanofiller was immersed in dilute nitric acid with a mass fraction of 10%~12% and mixed at 55~60℃ for 2~3 hours. After solid-liquid separation, washing and drying, acidified nanofiller was obtained.
[0033] Preferably, the mass fraction of the dilute nitric acid is 10% to 12%.
[0034] Preferably, the acidified nanofiller includes nano-silica and nano-attapulgite.
[0035] In this scheme, polyether polyols are used to simultaneously modify nano-silica and nano-attapulgite. The long molecular chains not only enhance the bonding force with the polymer matrix through physical entanglement, but their inherent flexible rubber segments also construct a flexible buffer layer between the inorganic nanoparticles and the organic matrix. The spherical nano-silica primarily provides rigidity and reinforcement, while the fibrous nano-attapulgite interweaves within the coating, producing synergistic toughening and thixotropic effects. This composite nanofiller system significantly improves the elongation at break, impact resistance, and anti-sagging properties of the coating film at low temperatures while achieving nano-reinforcement.
[0036] Preferably, the mass ratio of the nano-silica to the nano-attapulgite is (1~3):1.
[0037] Preferably, the amount of the polyether polyol used is 20% to 40% of the mass of the nanofiller.
[0038] Preferably, the polyether polyol is either polytetrahydrofuran diol or polyoxypropylene diol.
[0039] More preferably, the polyether polyol is polytetrahydrofuran diol.
[0040] Preferably, the particle size distribution of the nano-silica is 10~50nm.
[0041] Preferably, the fiber diameter of the nano-attapulgite is 20~50nm and the fiber length is 0.5~5μm.
[0042] Preferably, the amount of catalyst used is 0.4% to 0.5% of the mass of the polyether polyol.
[0043] Preferably, the catalyst is dibutyltin dilaurate.
[0044] Preferably, the additives include dispersants, defoamers, thickeners, film-forming agents, preservatives, and ultraviolet absorbers.
[0045] Preferably, the film-forming agent is a dodecyl alcohol ester.
[0046] Preferably, the rubber nanopowder is nitrile rubber nanopowder or chloroprene rubber nanopowder.
[0047] Preferably, the particle size distribution of the rubber nanoparticles is 50~200nm.
[0048] In this scheme, nitrile rubber nanopowder or chloroprene rubber nanopowder works synergistically with the elastic core of polyurethane-acrylate core-shell emulsion and the flexible segments of liquid polyisoprene to form a multi-scale stress buffer system in the coating film, which can effectively terminate and disperse microcracks, and further improve the fatigue resistance and impact resistance of the coating film under dynamic loads.
[0049] Preferably, the low-temperature resistant waterproof coating for the exterior walls of the building further includes 1-2 parts by weight of carbodiimide.
[0050] In this solution, by adding a specific waterborne carbodiimide, the carbodiimide functional groups can undergo mild bonding with the residual carboxyl groups in the polymer system, significantly enhancing the interfacial bonding force between phases, improving the density and cohesion of the coating film, thereby more effectively dispersing and absorbing stress, and synergistically improving the water resistance, mechanical strength and durability of the coating film.
[0051] Preferably, the low-temperature resistant waterproof coating for the exterior walls of the building further includes 3-5 parts by weight of microsilica powder and / or calcined kaolin.
[0052] More preferably, the silica powder and / or calcined kaolin undergoes the following pretreatment steps before use: S11: Add the ethanol-water solution of the silane coupling agent to the reactor, adjust the pH to 4.5~5.0, raise the temperature to 50~55℃, and hydrolyze for 60~70 min to obtain the pretreated solution; S12: Mix the pretreated liquid with silica powder and / or calcined kaolin at a solid-liquid mass ratio of (1.2~1.5):1, dry and disperse to obtain the final product.
[0053] Preferably, the particle size D50 of the microsilica powder is 0.1~5μm.
[0054] Preferably, the particle size D50 of the calcined kaolin is 1~10μm.
[0055] In this design, the spherical particles of microsilica achieve a relatively dense physical filling, laying the foundation for the high strength and shielding properties of the coating. The lamellar structure of calcined kaolin, through its directional arrangement, forms a labyrinthine barrier effect. Crucially, the surface modification layer forms a robust transition interface between the rigid filler and the flexible polymer matrix, not only improving dispersibility but also effectively transferring external stress from the matrix and dispersing it within the reinforcing skeleton. This simultaneously achieves a comprehensive improvement in the coating's strength, toughness, deformation resistance, and durability.
[0056] Secondly, this application also provides a preparation process for a low-temperature resistant waterproof coating for exterior walls of buildings, comprising the following steps: S1: Mix the composite solvent, the first part of the additives and the polyether polyol modified nanofiller evenly to obtain a homogeneous slurry; S2: Mix rubber nanopowder and liquid polyisoprene evenly to obtain an elastomer blend; S3: After mixing the modified silicone-acrylic emulsion and polyurethane-acrylate core-shell emulsion evenly, add the homogenizing slurry, elastomer blend, and the second part of the additives and mix evenly. Adjust the solid content, then add the remaining additives and adjust the pH to 7.5~8.5 to obtain a low-temperature resistant waterproof coating.
[0057] In this scheme, the preparation process first prepares a homogeneous slurry and elastomer blend, and then mixes it with the composite emulsion in steps. This ensures the uniform dispersion and stable existence of each functional component in the system, avoiding problems such as agglomeration and poor compatibility that may be caused by direct mixing of multiple components. This ensures the uniformity of the microstructure and the reliability of the performance of the final coating film.
[0058] Preferably, in step S3, after adjusting the pH, a step of adding carbodiimide is also included.
[0059] Preferably, in step S1, after the addition of the polyether polyol modified nanofiller, the step further includes the addition of microsilica powder and / or calcined kaolin.
[0060] In summary, this application has the following beneficial effects: This application uses modified silicone-acrylic emulsion and polyurethane-acrylate core-shell emulsion as film-forming matrix, providing a continuous phase that combines rigidity and flexibility. The toughening and reinforcing network constructed by rubber nanoparticles, liquid polyisoprene and nanofillers modified with polyether polyol flexible interface interpenetrates each other, which can effectively disperse stress under external force or low temperature, giving the coating film high elongation at break and low temperature resistance and flexibility. Detailed Implementation
[0061] The present application will be further described in detail below with reference to the embodiments.
[0062] The following preparation examples and embodiments specify the raw material specifications: The particle size distribution of nano-silica is 10~50nm; the fiber diameter of nano-attapulgite is 20~50nm and the fiber length is 0.5~5μm; the particle size distribution of nitrile rubber nanopowder is 50~200nm; the particle size distribution of chloroprene rubber nanopowder is 50-200nm; the particle size D50 of microsilica powder is 0.1~5μm; and the particle size D50 of calcined kaolin is 1~10μm.
[0063] The number-average molecular weight of polytetrahydrofuran diol is 2000 g / mol; the number-average molecular weight of polypropylene oxide diol is 1000 g / mol; and the number-average molecular weight of liquid polyisoprene is 25000~50000 g / mol.
[0064] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.
[0065] Preparation Examples 1-3: Modified Silicone-Acrylic Emulsions Preparation Example 1 The preparation method of the modified silicone-acrylic emulsion in this preparation example includes the following steps: Under a nitrogen atmosphere, 100g of deionized water, 50g of isopropanol, 50g of propylene glycol methyl ether, 2g of emulsifier DNS-86, and 2g of emulsifier CO-897 were added to a reaction vessel and stirred at 300 rpm until homogeneous. Then, 32g of trimethylolpropane diallyl ether and 12g of vinyltrimethoxysilane were added and stirred for 20 minutes. The mixture was then heated to 70°C, and an ammonium persulfate solution (1.6g of ammonium persulfate pre-dissolved in 10g of deionized water) was added. The mixture was stirred at 200 rpm for 90 minutes. The following two materials were then added dropwise simultaneously and at a uniform rate through two constant-pressure dropping funnels: Pre-emulsion: Add 240g butyl acrylate, 20g monobutyl maleate, 40g dodecafluoroheptyl methacrylate and 20g vinyl fluorosilicone oil to a mixer and mix thoroughly. Ammonium persulfate solution: Dissolve 2.8g of ammonium persulfate in 20g of deionized water beforehand; The dropping time is about 3 hours, during which the temperature is controlled at 70℃. After the dropping is completed, the temperature is raised to 80℃ and kept at that temperature for 2 hours. Then the system is cooled to 55℃ and distilled under reduced pressure at a vacuum of -0.08MPa until no distillate flows out. The system is then cooled to 40℃, filtered, and the solid content is adjusted to 55% using deionized water to obtain the modified silicone-acrylic emulsion.
[0066] Preparation Example 2 The preparation method of the modified silicone-acrylic emulsion in this preparation example includes the following steps: Under a nitrogen atmosphere, 100g of deionized water, 50g of isopropanol, 100g of propylene glycol methyl ether, 1g of emulsifier DNS-86, and 2g of emulsifier CO-897 were added to a reaction vessel and stirred at 300 rpm until homogeneous. Then, 48g of trimethylolpropane diallyl ether and 20g of vinyltrimethoxysilane were added and stirred for 30 minutes. The mixture was then heated to 80°C, and a potassium persulfate solution (1.5g of potassium persulfate pre-dissolved in 10g of deionized water) was added. The mixture was stirred at 200 rpm for 70 minutes. The following two materials were then added dropwise simultaneously and at a uniform rate through two constant-pressure dropping funnels: Pre-emulsion: Add 260g butyl acrylate, 30g monobutyl maleate, 50g dodecafluoroheptyl methacrylate and 32g vinyl fluorosilicone oil to a mixer and mix thoroughly. Potassium persulfate solution: Dissolve 2.0g of potassium persulfate in 20g of deionized water beforehand; The dropping time was approximately 3 hours, during which the temperature was controlled at 80°C. After the dropping was completed, the temperature was raised to 90°C and held for 1.5 hours. The system was then cooled to 55°C and subjected to vacuum distillation at a vacuum degree of -0.08 MPa until no distillate flowed out. The system was then cooled to 40°C, filtered, and the solid content was adjusted to 50% using deionized water to obtain the modified silicone-acrylic emulsion.
[0067] Preparation Example 3 The preparation method of the modified silicone-acrylic emulsion in this preparation example includes the following steps: Under a nitrogen atmosphere, 100g of deionized water, 50g of isopropanol, 100g of propylene glycol methyl ether, 3g of emulsifier DNS-86, and 2g of emulsifier CO-897 were added to a reaction vessel and stirred at 300 rpm until homogeneous. Then, 40g of trimethylolpropane diallyl ether and 16g of vinyltrimethoxysilane were added and stirred for 25 minutes. The mixture was then heated to 90°C, and a potassium persulfate solution (1.5g of potassium persulfate pre-dissolved in 10g of deionized water) was added. The mixture was stirred at 200 rpm for 80 minutes. The following two materials were then added dropwise simultaneously and at a uniform rate through two constant-pressure dropping funnels: Pre-emulsion: Add 250g butyl acrylate, 25g monobutyl maleate, 45g dodecafluoroheptyl methacrylate and 26g vinyl fluorosilicone oil to a mixer and mix thoroughly. Potassium persulfate solution: Dissolve 2.5g of potassium persulfate in 20g of deionized water beforehand; The dropping time was approximately 3 hours, during which the temperature was controlled at 90°C. After the dropping was completed, the temperature was maintained for 1 hour, and then the system was cooled to 55°C. Vacuum distillation was carried out under a vacuum of -0.08 MPa until no distillate flowed out. The system was then cooled to 40°C, filtered, and the solid content was adjusted to 55% using deionized water to obtain the modified silicone-acrylic emulsion.
[0068] Preparation Examples 4-6: Polyurethane-acrylate core-shell emulsions Preparation Example 4 The preparation method of the polyurethane-acrylate core-shell emulsion in this example includes the following steps: Under a nitrogen atmosphere, 50g of polytetrahydrofuran glycol, 25g of isophorone diisocyanate, 3g of dimethylolpropionic acid, 0.1g of dibutyltin dilaurate, and 40g of acetone were added to a reactor. The temperature was raised to 60℃, and the reaction was carried out for 4 hours. After cooling to 35℃, the pH was adjusted to 7.5 using triethylamine. The mixture was then added to 75g of deionized water containing 1.5g of emulsifier CO-436 while stirring at 1000 rpm. The temperature was raised to 70℃, and the following two materials were added dropwise simultaneously and at a uniform rate through two constant-pressure dropping funnels: Pre-emulsion: Add 25g butyl acrylate, 10g methyl methacrylate and 5g monobutyl maleate to a stirrer and stir until well mixed; Potassium persulfate solution: Dissolve 0.5g of potassium persulfate in 10g of deionized water beforehand; The dropping time was about 1 hour, during which the temperature was controlled at 70°C. After the dropping was completed, the temperature was raised to 80°C and kept at that temperature for another 1.5 hours. Then the system was cooled to 45°C and subjected to vacuum distillation at a vacuum degree of -0.08 MPa until no distillate flowed out. The system was then cooled to 40°C and the solid content was adjusted to 50% with deionized water to obtain a polyurethane-acrylate core-shell emulsion.
[0069] Preparation Example 5 The preparation method of the polyurethane-acrylate core-shell emulsion in this example includes the following steps: Under a nitrogen atmosphere, 60g of polytetrahydrofuran glycol, 35g of isophorone diisocyanate, 4g of dimethylolpropionic acid, 0.2g of dibutyltin dilaurate, and 50g of acetone were added to a reactor. The mixture was heated to 80℃ and reacted for 2 hours. After cooling to 35℃, the pH was adjusted to 7.5 using triethylamine. The mixture was then added to 100g of deionized water containing 2.0g of emulsifier CO-436 while stirring at 800 rpm. The mixture was stirred until homogeneous, and then heated to 80℃. The following two materials were then added dropwise simultaneously and at a uniform rate through two constant-pressure dropping funnels: Pre-emulsion: Add 30g butyl acrylate, 20g methyl methacrylate and 10g monobutyl maleate to a stirrer and mix thoroughly. Ammonium persulfate solution: Dissolve 0.5g of ammonium persulfate in 10g of deionized water beforehand; The dropping time was about 1 hour, during which the temperature was controlled at 80°C. After the dropping was completed, the temperature was raised to 90°C and kept at that temperature for another 2.5 hours. Then the system was cooled to 45°C and subjected to vacuum distillation at a vacuum degree of -0.08 MPa until no distillate flowed out. The system was then cooled to 40°C and the solid content was adjusted to 55% with deionized water to obtain a polyurethane-acrylate core-shell emulsion.
[0070] Preparation Example 6 The preparation method of the polyurethane-acrylate core-shell emulsion in this example includes the following steps: Under a nitrogen atmosphere, 55g of polytetrahydrofuran glycol, 30g of isophorone diisocyanate, 4g of dimethylolpropionic acid, 0.15g of dibutyltin dilaurate, and 50g of acetone were added to a reactor. The temperature was raised to 70℃, and the reaction was carried out for 3 hours. After cooling to 30℃, the pH was adjusted to 7.5 using triethylamine. The mixture was then added to 100g of deionized water containing 2.0g of emulsifier CO-436 while stirring at 800 rpm. The mixture was stirred until homogeneous, and the temperature was raised to 90℃. The following two materials were then added dropwise simultaneously and at a uniform rate through two constant-pressure dropping funnels: Pre-emulsion: Add 30g butyl acrylate, 15g methyl methacrylate and 10g monobutyl maleate to a stirrer and mix thoroughly. Potassium persulfate solution: Dissolve 0.55g of potassium persulfate in 10g of deionized water beforehand; The dropping time was about 1 hour, during which the temperature was controlled at 90℃. After the dropping was completed, the temperature was maintained for another 2 hours. Then the system was cooled to 45℃ and distilled under reduced pressure at a vacuum of -0.08MPa until no distillate flowed out. The system was then cooled to 40℃ and the solid content was adjusted to 55% with deionized water to obtain a polyurethane-acrylate core-shell emulsion.
[0071] Preparation Examples 7-9: Polyether Polyol Modified Nanofillers Preparation Example 7 The preparation method of the polyether polyol modified nanofiller in this example includes the following steps: Nano-silica and nano-attapulgite in a mass ratio of 1:1 were immersed in 10% dilute nitric acid, heated to 60°C, stirred and mixed for 2 hours, centrifuged, washed with deionized water until neutral, and dried at 50°C to constant weight to obtain acidified nanofiller. Under a nitrogen atmosphere, 50g of acidified nanofiller was added to 200g of toluene and stirred at 800r / min for 30min. Then, 0.05g of dibutyltin dilaurate was added and mixed evenly. Next, 10g of polypropylene glycol was added and mixed evenly. The mixture was heated to 80℃ and reacted for 6h. After cooling to room temperature, the mixture was centrifuged, washed twice with toluene, washed with deionized water until neutral, and dried at 50℃ to constant weight to obtain polyether polyol modified nanofiller.
[0072] Preparation Example 8 The preparation method of the polyether polyol modified nanofiller in this example includes the following steps: Nano-silica and nano-attapulgite clay in a mass ratio of 3:1 were immersed in 12% dilute nitric acid, heated to 55°C, stirred and mixed for 2 hours, centrifuged, washed with deionized water until neutral, and dried at 50°C to constant weight to obtain acidified nanofiller. Under a nitrogen atmosphere, 50g of acidified nanofiller was added to 200g of toluene and stirred at 800r / min for 30min. Then, 0.08g of dibutyltin dilaurate was added and mixed evenly. Next, 20g of polytetrahydrofuran glycol was added and mixed evenly. The mixture was heated to 100℃ and reacted for 4h. After cooling to room temperature, the mixture was centrifuged, washed twice with toluene, washed with deionized water until neutral, and dried at 50℃ to constant weight to obtain polyether polyol modified nanofiller.
[0073] Preparation Example 9 The preparation method of the polyether polyol modified nanofiller in this example includes the following steps: Nano-silica and nano-attapulgite in a mass ratio of 2:1 were immersed in 10% dilute nitric acid, heated to 55°C, stirred and mixed for 3 hours, centrifuged, washed with deionized water until neutral, and dried at 50°C to constant weight to obtain acidified nanofiller. Under a nitrogen atmosphere, 50g of acidified nanofiller was added to 200g of toluene and stirred at 800r / min for 30min. Then, 0.06g of dibutyltin dilaurate was added and mixed evenly. Next, 15g of polytetrahydrofuran glycol was added and mixed evenly. The mixture was heated to 90℃ and reacted for 5h. After cooling to room temperature, the mixture was centrifuged, washed twice with toluene, washed with deionized water until neutral, and dried at 50℃ to constant weight to obtain polyether polyol modified nanofiller.
[0074] Example 1 The preparation process of the low-temperature resistant waterproof coating for building exterior walls in this embodiment includes the following steps: S1: Add 60g of composite solvent, 2g of dispersant, 1g of defoamer, and 40g of polyether polyol modified nanofiller to a stirrer and stir at 800r / min for 30min to obtain a homogeneous slurry. S2: Add 15g of chloroprene rubber nanopowder and 10g of liquid polyisoprene to a stirrer and stir at 800r / min for 30min to obtain an elastomer blend. S3: Add 200g of modified silicone-acrylic emulsion and 75g of polyurethane-acrylate core-shell emulsion to a mixer and stir at 300r / min for 15min. Add homogenizing slurry and elastomer blend and stir for 15min. Then add 12g of film-forming agent and stir for 15min. Adjust the solid content to 50% with deionized water and slowly add 4g of thickener. Continue stirring for 15min. Add 1g of preservative and 2g of UV absorber and continue stirring for 10min. Adjust the pH to 7.5 with triethylamine, add 0.5g of defoamer, and stir at 150r / min for 5min to obtain a low-temperature resistant waterproof coating.
[0075] The additives include 2g dispersant, 1.5g defoamer, 4g thickener, 12g film-forming agent, 1g preservative, and 2g UV absorber; specifically: the dispersant is a polycarboxylate dispersant; the defoamer is a polyether-modified silicone defoamer; the thickener is a hydrophobically modified polyurethane rheology thickener; the film-forming agent is dodecyl alcohol ester; the preservative is isothiazolinone; and the UV absorber is benzotriazole. The compound solvent consists of 24g deionized water, 24g propylene glycol methyl ether, and 12g isopropanol; The modified silicone-acrylic emulsion was from Preparation Example 1; the polyurethane-acrylate core-shell emulsion was from Preparation Example 4; and the polyether polyol modified nanofiller was from Preparation Example 7.
[0076] Example 2 The preparation process of the low-temperature resistant waterproof coating for building exterior walls in this embodiment includes the following steps: S1: Add 100g of composite solvent, 3g of dispersant, 2g of defoamer, and 60g of polyether polyol modified nanofiller to a stirrer and stir at 800r / min for 30min to obtain a homogeneous slurry. S2: Add 25g of chloroprene rubber nanopowder and 20g of liquid polyisoprene to a stirrer and stir at 800r / min for 30min to obtain an elastomer blend. S3: Add 250g of modified silicone-acrylic emulsion and 125g of polyurethane-acrylate core-shell emulsion to a mixer and stir at 300r / min for 15min. Add homogenizing slurry and elastomer blend and stir for 15min. Then add 16g of film-forming agent and stir for 15min. Adjust the solid content to 50% with deionized water and slowly add 6g of thickener. Continue stirring for 15min. Add 2g of preservative and 4g of UV absorber and continue stirring for 10min. Adjust the pH to 8.5 with triethylamine, add 1g of defoamer, and stir at 150r / min for 5min to obtain a low-temperature resistant waterproof coating.
[0077] The additives include 3g dispersant, 3g defoamer, 6g thickener, 16g film-forming agent, 2g preservative, and 4g UV absorber; specifically: the dispersant is a polycarboxylate dispersant; the defoamer is a polyether-modified silicone defoamer; the thickener is a hydrophobically modified polyurethane rheology thickener; the film-forming agent is dodecyl alcohol ester; the preservative is isothiazolinone; and the UV absorber is benzotriazole. The compound solvent consists of 50g deionized water, 25g propylene glycol methyl ether, and 25g isopropanol; The modified silicone-acrylic emulsion was from Preparation Example 2; the polyurethane-acrylate core-shell emulsion was from Preparation Example 5; and the polyether polyol modified nanofiller was from Preparation Example 8.
[0078] Example 3 The preparation process of the low-temperature resistant waterproof coating for building exterior walls in this embodiment includes the following steps: S1: Add 80g of composite solvent, 2.5g of dispersant, 1.5g of defoamer, and 50g of polyether polyol modified nanofiller to a stirrer and stir at 800r / min for 30min to obtain a homogeneous slurry. S2: Add 20g of nitrile rubber nanopowder and 15g of liquid polyisoprene to a stirrer and stir at 800r / min for 30min to obtain an elastomer blend. S3: Add 230g of modified silicone-acrylic emulsion and 100g of polyurethane-acrylate core-shell emulsion to a mixer and stir at 300r / min for 15min. Add homogenizing slurry and elastomer blend and stir for 15min. Then add 14g of film-forming agent and stir for 15min. Adjust the solid content to 50% with deionized water and slowly add 5g of thickener. Continue stirring for 15min. Add 1.5g of preservative and 3g of UV absorber and continue stirring for 10min. Adjust the pH to 8.0 with triethylamine, add 1g of defoamer, and stir at 150r / min for 5min to obtain a low-temperature resistant waterproof coating.
[0079] The additives include 2.5g dispersant, 2.5g defoamer, 5g thickener, 14g film-forming agent, 1.5g preservative, and 3g UV absorber; specifically: the dispersant is a polycarboxylate dispersant; the defoamer is a polyether-modified silicone defoamer; the thickener is a hydrophobically modified polyurethane rheology thickener; the film-forming agent is dodecyl alcohol ester; the preservative is isothiazolinone; and the UV absorber is benzotriazole. The compound solvent consists of 50g deionized water, 35g propylene glycol methyl ether, and 15g isopropanol; The modified silicone-acrylic emulsion was from Preparation Example 3; the polyurethane-acrylate core-shell emulsion was from Preparation Example 6; and the polyether polyol modified nanofiller was from Preparation Example 9.
[0080] Example 4 The difference between this embodiment and embodiment 3 is as follows: S3: Add 230g of modified silicone-acrylic emulsion and 100g of polyurethane-acrylate core-shell emulsion to a mixer and stir at 300r / min for 15min. Add homogenizing slurry and elastomer blend and stir for 15min. Then add 14g of film-forming agent and stir for 15min. Adjust the solid content to 50% with deionized water and slowly add 5g of thickener. Continue stirring for 15min. Add 1.5g of preservative and 3g of UV absorber and continue stirring for 10min. Adjust the pH to 8.0 with triethylamine and add 1g of carbodiimide. Stir at 150r / min for 10min. Add 1g of defoamer and stir at 150r / min for 5min to obtain a low-temperature resistant waterproof coating.
[0081] Everything else is the same as in Example 3.
[0082] Example 5 The difference between this embodiment and embodiment 4 is that: S1: Add 80g of composite solvent, 2.5g of dispersant, 1.5g of defoamer, 50g of polyether polyol modified nanofiller and 3g of microsilica powder to a stirrer and stir at 800r / min for 30min to obtain a homogeneous slurry. Before using microsilica powder, the following pretreatment steps are required: Add 0.08g of silane coupling agent KH560 to 10g of ethanol aqueous solution, adjust the pH to 5.0 with 5% acetic acid, heat to 50℃, stir and hydrolyze for 60min to obtain the pretreated solution; Place 3g of silica powder in a container, slowly add 3.6g of the above pretreatment liquid while stirring at 150r / min, and continue stirring to mix it evenly. Then transfer it to a 50℃ drying oven to dry to constant weight, lightly grind and disperse, and set aside for later use.
[0083] In the ethanol-water solution, the volume ratio of ethanol to deionized water is 1:1.
[0084] The rest is the same as in Example 4.
[0085] Example 6 The difference between this embodiment and embodiment 5 is as follows: S1: Add 80g of composite solvent, 2.5g of dispersant, 1.5g of defoamer, 50g of polyether polyol modified nanofiller, 3g of microsilica powder and 2g of calcined kaolin to a stirrer and stir at 800r / min for 30min to obtain a homogeneous slurry. Before use, silica fume and calcined kaolin undergo the following pretreatment steps: Add 0.15g of silane coupling agent KH560 to 15g of ethanol aqueous solution, adjust the pH to 4.5 with 5% acetic acid, heat to 55℃, stir and hydrolyze for 70min to obtain the pretreated solution. Place 3g of silica powder and 2g of calcined kaolin in a container, slowly add 7.5g of the above pretreatment liquid while stirring at 150r / min, and continue stirring to mix evenly. Then transfer to a 50℃ drying oven to dry to constant weight, lightly grind and disperse, and set aside for later use.
[0086] In the ethanol-water solution, the volume ratio of ethanol to deionized water is 1:1.
[0087] The rest is the same as in Example 5.
[0088] Example 7 The difference between this embodiment and embodiment 5 is as follows: The amount of carbodiimide used is 2g.
[0089] The rest is the same as in Example 5.
[0090] Comparative Example 1 The difference between this comparative example and Example 1 is as follows: The polyether polyol modified nanofiller was replaced with silanized nanofiller of equal mass. The preparation method of silanized nanofillers includes the following steps: Take 50g of a premix of nano-silica and nano-attapulgite in a mass ratio of 1:1, add it to the reactor, then add 200g of ethanol aqueous solution, stir and mix at a stirring speed of 1000r / min for 30min, then add 6g of silane coupling agent KH560, adjust the stirring speed to 300r / min, stir and mix evenly, adjust the pH to 5.0 with 10% acetic acid, raise the temperature to 55℃, stir and mix for 4h, centrifuge, wash once with anhydrous ethanol, wash with deionized water until neutral, and dry at 60℃ to constant weight to obtain silanized nanofiller.
[0091] Everything else is the same as in Example 1.
[0092] Comparative Example 2 The difference between this comparative example and Example 1 is as follows: The preparation method of this comparative modified silicone-acrylic emulsion includes the following steps: Under a nitrogen atmosphere, 100g deionized water, 50g isopropanol, 50g propylene glycol methyl ether, 2g emulsifier DNS-86, and 2g emulsifier CO-897 were added to a reactor and stirred at 300 rpm until homogeneous. Then, 32g trimethylolpropane diallyl ether, 12g vinyltrimethoxysilane, 240g butyl acrylate, 20g monobutyl maleate, 40g dodecafluoroheptyl methacrylate, and 20g vinyl fluorosilicone oil were added, and stirring continued. Mix for 20 minutes, heat to 70°C, add potassium persulfate solution (4.4 g potassium persulfate pre-dissolved in 30 g deionized water), stir at 200 r / min for 4.5 h, heat to 80°C, keep at this temperature for 2 h, then cool the system to 55°C, and perform vacuum distillation at -0.08 MPa until no distillate flows out. Cool to 40°C, filter, and adjust the system to a solid content of 55% using deionized water to obtain modified silicone-acrylic emulsion.
[0093] Everything else is the same as in Example 1.
[0094] Comparative Example 3 The preparation method of the modified silicone-acrylic emulsion in this comparative example includes the following steps: Under a nitrogen atmosphere, 100g of deionized water, 50g of isopropanol, 50g of propylene glycol methyl ether, 2g of emulsifier DNS-86, and 2g of emulsifier CO-897 were added to a reaction vessel and stirred at 300 rpm until homogeneous. Then, 32g of trimethylolpropane diallyl ether and 12g of vinyltrimethoxysilane were added and stirred for 20 minutes. The mixture was then heated to 70°C, and a potassium persulfate solution (1.6g of potassium persulfate pre-dissolved in 10g of deionized water) was added. The mixture was stirred at 200 rpm for 90 minutes. The following two materials were then added dropwise simultaneously and at a uniform rate through two constant-pressure dropping funnels: Pre-emulsion: Add 240g butyl acrylate, 40g dodecafluoroheptyl methacrylate and 20g vinyl fluorosilicone oil to a mixer and mix thoroughly. Potassium persulfate solution: Dissolve 2.8g of potassium persulfate in 20g of deionized water beforehand; The dropping time is about 3 hours, during which the temperature is controlled at 70℃. After the dropping is completed, the temperature is raised to 80℃ and kept at that temperature for 2 hours. Then the system is cooled to 55℃ and distilled under reduced pressure at a vacuum of -0.08MPa until no distillate flows out. The system is then cooled to 40℃, filtered, and the solid content is adjusted to 55% using deionized water to obtain the modified silicone-acrylic emulsion.
[0095] Comparative Example 4 The difference between this comparative example and Example 1 is as follows: The preparation method of this comparative polyurethane-acrylate core-shell emulsion includes the following steps: Under a nitrogen atmosphere, 50g of polytetrahydrofuran glycol, 25g of isophorone diisocyanate, 0.1g of dibutyltin dilaurate, and 40g of acetone were added to a reactor. The mixture was heated to 60℃ and reacted for 4 hours. After cooling to 35℃, the pH was adjusted to 7.5 using triethylamine. The mixture was then added to 75g of deionized water containing 1.5g of emulsifier CO-436 while stirring at 1000 rpm. The mixture was stirred until homogeneous, and then heated to 70℃. The following two materials were then added dropwise simultaneously and at a uniform rate through two constant-pressure dropping funnels: Pre-emulsion: Add 25g butyl acrylate and 10g methyl methacrylate to a mixer and mix thoroughly. Potassium persulfate solution: Dissolve 0.5g of potassium persulfate in 10g of deionized water beforehand; The dropping time was about 1 hour, during which the temperature was controlled at 70°C. After the dropping was completed, the temperature was raised to 80°C and kept at that temperature for another 1.5 hours. Then the system was cooled to 45°C and subjected to vacuum distillation at a vacuum degree of -0.08 MPa until no distillate flowed out. The system was then cooled to 40°C and the solid content was adjusted to 55% with deionized water to obtain a polyurethane-acrylate core-shell emulsion.
[0096] Everything else is the same as in Example 1.
[0097] Comparative Example 5 The difference between this comparative example and Example 1 is as follows: The polyurethane-acrylate core-shell emulsion was replaced with a modified silicone-acrylic emulsion of equal mass.
[0098] Everything else is the same as in Example 1.
[0099] Performance testing Standard samples were prepared for the low-temperature resistant waterproof coatings obtained in Examples 1-7 and Comparative Examples 1-5, according to the test items: (1) The coating was evenly applied to the surface of the standard cement mortar board, and the dry film thickness was controlled at (100±10) μm. After surface drying under the standard conditions of (23±2)℃ and (50±5)% relative humidity, it was transferred to a (5±1)℃ low temperature chamber for curing for 48h. Subsequently, the sample was cured for 7 days under the standard conditions of (23±2)℃ and (50±5)% relative humidity. (2) Pour the coating onto a flat polytetrafluoroethylene plate and use a scraper to control the thickness to prepare a uniform coating film. Cure it for 7 days under standard conditions of (23±2)℃ and (50±5)% relative humidity. After it is fully cured, peel off the coating film and cut it into samples of the specified size with a standard dumbbell-shaped cutter.
[0100] Then, performance testing was conducted, and the results are shown in Table 1. The reference standards are as follows: Adhesion: GB / T 5210-2006; Tensile strength and elongation at break: GB / T 16777-2008; Water resistance: GB / T 1733-1993.
[0101] Table 1. Performance test data of the low-temperature resistant waterproof coatings prepared in Examples 1-7 and Comparative Examples 1-5
[0102] Analysis of the performance test data of the samples prepared in Comparative Examples 1-5 and Example 1 shows that: Comparative Example 1 uses silanized nanofillers. Due to their strong interfacial rigidity, their adhesion and flexibility are insufficient, resulting in microcracks during low-temperature bending and a loss of elongation at break. Comparative Example 2 may have an excessively wide molecular weight distribution due to the synthesis process, leading to deterioration in adhesion, mechanical strength, and water resistance. Comparative Examples 3 and 4 lack carboxyl-containing monomers, which weakens the stability of the emulsion and the interfacial bonding between components, resulting in insufficient film density, significantly worse water resistance, and reduced adhesion. Comparative Example 5 uses only silicone-acrylic emulsion, which has high adhesion and tensile strength, but lacks the elasticity provided by polyurethane, resulting in low elongation at break and poor low-temperature bending performance.
[0103] Analysis of the performance test data of the samples prepared in Examples 1-7 shows that by introducing carbodiimide and adding silane-treated microsilica powder and calcined kaolin, the tensile strength of the coating film was gradually improved. Simultaneously, with a moderate increase in crosslinking density and rigid particle content, the mobility of the polymer molecular chains was somewhat limited, resulting in a slow decrease in elongation at break. The samples prepared in Examples 1-7, through optimized interface design, maintained relatively high adhesion while improving strength and stiffness, and also exhibited excellent low-temperature flexibility and water resistance.
[0104] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A low-temperature resistant waterproof coating for exterior walls of buildings, characterized in that, It is prepared from the following raw materials in parts by weight: 200-250 parts of modified silicone-acrylic emulsion, 75-125 parts of polyurethane-acrylate core-shell emulsion, 40-60 parts of polyether polyol modified nanofiller, 15-25 parts of rubber nanopowder, 10-20 parts of liquid polyisoprene, 22-34 parts of additives and 60-100 parts of composite solvent. The modified silicone-acrylic emulsion is specifically prepared by prepolymerizing a polyhydroxy compound containing double bonds and a silane coupling agent containing double bonds, and then copolymerizing it with acrylate monomer A and vinyl fluorosilicone oil. The polyurethane-acrylate core-shell emulsion is specifically formulated by prepolymerizing polyether polyol, isocyanate, and carboxyl-containing hydrophilic monomer, followed by copolymerization with acrylate monomer B.
2. The low-temperature resistant waterproof coating for exterior walls of buildings according to claim 1, characterized in that, The preparation method of the modified silicone-acrylic emulsion includes the following steps: Under an inert atmosphere, the composite solvent and emulsifier are mixed evenly, then a polyhydroxy compound containing double bonds and a silane coupling agent containing double bonds are added and mixed evenly. The mixture is heated to 70-90°C, a portion of the initiator is added, and the reaction is carried out for 60-90 minutes. Then, acrylate monomer A, vinyl fluorosilicone oil and the remaining initiator are added, and the mixture is kept at this temperature for 4-5 hours. After vacuum distillation and cooling, the solid content is adjusted to obtain the modified silicone-acrylic emulsion.
3. The low-temperature resistant waterproof coating for exterior walls of buildings according to claim 2, characterized in that, The polyhydroxy compound containing a double bond is either trimethylolpropane diallyl ether or pentaerythritol triallyl ether.
4. The low-temperature resistant waterproof coating for exterior walls of buildings according to claim 2, characterized in that, The acrylate monomer A includes butyl acrylate, monobutyl maleate, and dodecafluoroheptyl methacrylate.
5. The low-temperature resistant waterproof coating for exterior walls of buildings according to claim 1, characterized in that, The preparation method of the polyurethane-acrylate core-shell emulsion includes the following steps: Under an inert atmosphere, polyether polyol, isocyanate, carboxyl-containing hydrophilic monomer, catalyst, and acetone are added to a reactor, heated to 60-80°C, reacted for 2-4 hours, cooled, and the pH is adjusted to 7.5-8.
0. The mixture is then added to water containing emulsifier, mixed thoroughly, heated to 70-90°C, acrylate monomer B and initiator are added, and the mixture is kept at this temperature for 2.5-3.5 hours. The mixture is then distilled under reduced pressure, cooled, and the solid content is adjusted to obtain a polyurethane-acrylate core-shell emulsion.
6. The low-temperature resistant waterproof coating for exterior walls of buildings according to claim 5, characterized in that, The acrylate monomer B includes butyl acrylate, methyl methacrylate, and monobutyl maleate.
7. The low-temperature resistant waterproof coating for exterior walls of buildings according to claim 1, characterized in that, The preparation method of the polyether polyol modified nanofiller includes the following steps: Under an inert atmosphere, the acidified nanofiller is uniformly dispersed in an organic solvent, a catalyst is added and mixed evenly, then polyether polyol is added and mixed evenly. The mixture is heated to 80~100℃ and reacted for 4~6 hours. After cooling, solid-liquid separation is performed, followed by washing and drying to obtain polyether polyol modified nanofiller.
8. The low-temperature resistant waterproof coating for exterior walls of buildings according to claim 7, characterized in that, The acidified nanofiller includes nano-silica and nano-attapulgite.
9. The low-temperature resistant waterproof coating for exterior walls of buildings according to claim 1, characterized in that, The polyether polyol is either polytetrahydrofuran diol or polyoxypropylene diol.
10. A preparation process for a low-temperature resistant waterproof coating for exterior walls of buildings as described in any one of claims 1 to 9, characterized in that, The steps include the following: S1: Mix the composite solvent, the first part of the additives, and the polyether polyol modified nanofiller evenly to obtain a homogeneous slurry; S2: Mix rubber nanopowder and liquid polyisoprene evenly to obtain an elastomer blend; S3: After mixing the modified silicone-acrylic emulsion and polyurethane-acrylate core-shell emulsion evenly, add the homogenizing slurry, elastomer blend, and the second part of the additives and mix evenly. Adjust the solid content, then add the remaining additives and adjust the pH to 7.5~8.5 to obtain a low-temperature resistant waterproof coating.
Citation Information
Patent Citations
Nano anti-corrosion waterproof coating capable of resisting high temperature, low temperature, acid and alkali
CN119570324A
Sprayed fast setting liquid rubber waterproof paint applicable to severe cold regions and preparation method
CN107903820A
Vinyl polymer latex systems
US5118752A
Cited By
Silicon nano inorganic flame-retardant thermal-insulation coating and preparation method thereof
CN121471775A